Sorting out the mixed economy : the rise and fall of welfare and developmental states in the Americas - Offner, Amy C. (Histories of economic life., 2019)
"The untold story of how U.S. development efforts in postwar Latin America helped lead to the dismantling of the U.S. welfare state. ... In this groundbreaking book, Amy Offner brings readers to Colombia and back, showing the entanglement of American societies and the contradictory promises of midcentury statebuilding. The untold story of how the road from the New Deal to the Great Society ran through Latin America, Sorting Out the Mixed Economy also offers a surprising new account of the origins of neoliberalism."